Deep brain stimulation in 18 patients with severe Gilles de la Tourette syndrome refractory to treatment: the surgery and stimulation. Issue 2 (10th September 2007) - Servello, D; Porta, M; Sassi, M; Brambilla, A; Robertson, M M
Abstract : Background: There have been several reports of successful deep brain stimulation (DBS) for the treatment of severe Gilles de la Tourette syndrome (GTS). Method: 18 cases of GTS who were resistant to at least 6 months of standard and innovative treatments, as well as to psychobehavioural techniques, underwent DBS. DBS was placed bilaterally in the centromedian–parafascicular (CM–Pfc) and ventralis oralis complex of the thalamus. Patients were evaluated after surgery, with immediate and formal assessments at least every 3 months, including "on–off" and "sham off" in the first nine patients. Results: All patients responded well to DBS, although to differing degrees. The duration of follow-up assessments ranged from 3 to 18 months. The comorbid symptoms of obsessive–compulsive behaviour, obsessive–compulsive disorder, self-injurious behaviours, anxiety and premonitory sensations decreased after treatment with DBS. There were no serious permanent adverse effects. Conclusions: DBS is a useful and safe treatment for severe GTS. The results of ours and previous DBS reports suggest that the CM–Pfc and ventralis oralis complex of the thalamus may be a good DBS target for GTS.